Differential Equations: (3y - 2yx^2)[ 1 + ln^2 (2x^3 / 3y^2) ] dx - 2x dy = 0

3 posts / 0 new
Last post
agentcollins
Differential Equations: (3y - 2yx^2)[ 1 + ln^2 (2x^3 / 3y^2) ] dx - 2x dy = 0

The topic is Additional Topics in Ordinary DE of the first order. Thank you so much.

3y-2yx^2 [ 1 + (ln (2x^3 / 3y^2))^2 ]dx - 2xdy =0

Rate: 
0
No votes yet
Jhun Vert
Jhun Vert's picture

do you mean this?

(3y-2yx^2)[ 1 + (ln (2x^3 / 3y^2))^2 ]dx - 2xdy =0

Rate: 
0
No votes yet
agentcollins

[(3y-2yx^2) [ 1 + (ln (2x^3 / 3y^2))^2 ]]dx - 2xdy =0

Rate: 
0
No votes yet